Talent Accelerator: Understanding How Talent Delivers Performance for Asian Firms. (June 2014) - Ulrich, Dave; Allen, Justin
Throughout the last 15 years of economic roller coaster rides, Asian countries have clearly led the world in economic growth. Success in Asia has been due, in part, to the transformation many Asian economies have engineered, moving beyond manufacturing to successfully exporting technology and services. Now another revolution is afoot. The best performing Asian businesses are gaining impressive premiums in value creation because they have learned and implemented the secrets of leveraging their company's most essential resource: talent. To better understand this talent trend and how investment in talent ties to business results in top Asian companies, we gathered data from over 570 separate businesses in Singapore, China and India about 13 talent management processes. We, then, show the relative impact of these 13 talent management practices on business performance as moderated by the strategy and growth patterns of the firm. We found that investments in managing current talent have more impact on business performance than hiring new talent or retaining existing talent. We report variances in the impact of talent management depending on country, strategy and growth pattern. We discuss implications for talent management for line managers and HR professionals. Ultimately, this work will inform those charged with managing talent so that they can accelerate the use of talent to deliver business results.